(Mis)Attributing the Causes of American Job Loss: The Consequences of Getting It Wrong. Issue 1 (28th June 2021) - Mutz, Diana C
Abstract: What difference does it make if people attribute the loss of manufacturing jobs to trade as opposed to automation? Attributions of responsibility for social problems help shape mass opinion. In this study I use two experiments, including one nationally representative probability survey-experiment, to examine the consequences of attributing job loss to trade versus automation. Findings suggest that as of 2018, public discourse attributes manufacturing job loss in America primarily to trade. When I experimentally manipulate attributions of responsibility for job loss, I find important consequences for levels of mass support for international trade, the extent of negative emotions arising from job loss, and beliefs that trade restrictions and tariffs can bring back manufacturing jobs. Finally, job loss that is attributed to trade—even when it is a single job loss—also serves as a threat to the national ingroup, which triggers a heightened sense of national superiority among white Americans.